The Effect of Liquidity and Leverage on Profitability, with Company Size as a Moderating Variable, in Companies in the Automotive Subsector (Automobiles & Components) Listed on the Indonesia Stock Exchange - Ade Saefu Rohman; Maiyaliza Maiyaliza (Publikasi Indonesia, 2026)
This research examines the effect of liquidity and leverage on profitability, with firm size as a moderating variable, in automotive subsector companies listed on the Indonesia Stock Exchange (IDX). The research was motivated by the fluctuating financial performance of the automotive industry during the post-pandemic recovery period, particularly regarding liquidity management, debt utilization, and profitability achievement. This research aims to analyze the influence of liquidity, proxied by the Current Ratio (CR), and leverage, proxied by the Debt-to-Equity Ratio (DER), on profitability measured by Return on Assets (ROA), as well as the moderating role of firm size. The research employed a quantitative associative approach using secondary data obtained from annual financial reports of automotive and component companies listed on the IDX during 2018–2024. The sample consisted of five companies selected through purposive sampling, resulting in 30 observations after outlier elimination. Data analysis was conducted using Moderated Regression Analysis (MRA). The results indicate that liquidity and leverage have a positive and significant effect on profitability. Furthermore, firm size significantly moderates and strengthens the relationship between liquidity and profitability as well as the relationship between leverage and profitability. These findings imply that companies with effective working capital management, optimal debt structures, and larger asset capacities tend to achieve higher profitability levels. The study supports the Working Capital Theory and Trade-Off Theory in explaining corporate financial performance in the automotive industry.